A Poet of our Times: Charles Simic’s Poetry and Poetics as an Interpretation of the World - Raggio, Marcela María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
Charles Simic has been writing and publishing for decades, has been America's Poet Laureate, and is one of the best well-known voices in American literature. All this could be explained by the fact that Simic writes in, from, and about the contemporary world with an ironic view that speaks straightforwardly to readers. Thus, the translation of his works as part of a literary-cultural exchange and as part of literary and intellectual nets, has gained relevance in Spain. Yet, in the Latin American context, Simic is known only by a few translations in poetry magazines and literary journals. Reading his works and understanding his poetics may foster knowledge about Simic in Latin America, by proposing alternative versions to those produced in Spain, for readers on this side of the Atlantic. This may show the public that Simic “reads” and interprets our century through his poetry, beyond the U.S. Borders.